Pengaruh Intensitas Persaingan Pasar, Strategi dan Ketidakpastian Lingkungan yang Dirasakan Terhadap Penggunaan Informasi Sistem Akuntansi Manajemen dan Kinerja Unit Bisnis - Faisal Faisal; Tri Jatmiko Wahyu Prabowo (Jurnal Akuntansi dan Auditing Indonesia, 2006)
This study examines the impact of intensity of market competition, strategy and per¬ceived environmental uncertainty (PEU) on the usage of information in management accounting system (MAS) and unit business performance. In this research MAS is viewed as a system which provides benchmark and monitor information in addition to internal and historical information traditionally generated by management accounting system. Data analyzed by using structural equation modeling indicate that the usage of infor¬mation in management accounting system (SAM) acts as a mediator in the relationship between intensity of market competition, perceived environmental un¬certainty (PEU) and unit business performance. On the other hand, the relationship between strategy and unit business performance through SAM is not significant.Keywords:    intensity of market competition, perceived environmental uncertainty (PEU), strategy, management accounting system (MAS), unit business performance.